A new HLA‐B allele, HLA‐B*35:481. (4th June 2021) - Miotti, Valeria; Battarra, Mariarosa; Sindici, Chiara; Londero, Donatella; Andreani, Marco
Abstract : The novel allele HLA‐B*35:481 differs from HLA‐B*35:05:01 by two nucleotide substitution in exon 3.